Prior Trichinella spiralis infection protects against Schistosoma mansoni induced hepatic fibrosis - El-kady, Asmaa M.; Altwaim, Sarah A.; Wakid, Majed H.; Banjar, Alaa S.; Mohammed, Khalil; Alfaifi, Mashael S.; Elshazly, Hayam; Al-Megrin, Wafa Abdullah I.; Alshehri, Eman Abdullah; Sayed, Eman; Elshabrawy, Hatem A. (Frontiers in Veterinary Science, 2024)
BackgroundSchistosomiasis affects approximately 250 million people worldwide, with 200,000 deaths annually. It has been documented that the granulomatous response to Schistosoma mansoni (S. mansoni) oviposition is the root cause of progressive liver fibrosis in chronic infection, in 20% of the patients, and can lead to liver cirrhosis and/or liver cancer. The influence of helminths coinfection on schistosomiasis-induced liver pathological alterations remains poorly understood. Therefore, in this study, we investigated the effect of Trichinella spiralis (T. spiralis) infection on S. mansoni-induced hepatic fibrosis.Materials and methodsThirty adult male Balb-c mice were divided into three groups. Group 1 was left uninfected; group 2 was infected with S. mansoni cercariae and group 3 was orally infected with T. spiralis larvae, then 28 days later, this group was infected with S. mansoni cercariae. All groups were sacrificed at the end of the 8th week post infection with S. mansoni to evaluate the effect of pre-infection with T. spiralis on S. mansoni induced liver fibrosis was evaluated parasitologically (worm burden and egg count in tissues), biochemically (levels of alanine aminotransferase and aspartate aminotransferase), histopathologically (H&E and MT staining, and immunohistochemical staining for the expression of α-SMA, IL-6, IL-1β, IL-17, IL-23, TNF-α, and TGF-β).ResultsThe results in the present study demonstrated marked protective effect of T. spiralis against S. mansoni induced liver pathology. We demonstrated that pre-infection with T. spirais caused marked reduction in the number of S. mansoni adult worms (3.17 ± 0.98 vs. 18 ± 2.16, P = 0.114) and egg count in both the intestine (207.2 ± 64.3 vs. 8,619.43 ± 727.52, P = 0.009) and liver tissues (279 ± 87.2 vs. 7,916.86 ± 771.34; P = 0.014). Consistently, we found significant reductions in both number (3.4 ± 1.1 vs. 11.8.3 ± 1.22; P = 0.007) and size (84 ± 11 vs. 294.3 ± 16.22; P = 0.001) of the hepatic granulomas in mice pre-infected with T. spiralis larvae compared to those infected with only S. mansoni. Furthermore, pre- infection with T. spiralis markedly reduced S. mansoni- induced hepatic fibrosis, as evidenced by decreased collagen deposition, low expression of α-SMA, and significantly reduced levels of IL-17, IL-1B, IL-6, TGF-B, IL-23, and TNF-α compared to mice infected with S. mansoni only.ConclusionsOur data show that pre-infection with T. spiralis effectively protected mice from severe schistosomiasis and liver fibrosis. We believe that our findings support the potential utility of helminths for the preventing and ameliorating severe pathological alterations induced by schistosomiasis.